2008
DOI: 10.1364/oe.16.020448
|View full text |Cite
|
Sign up to set email alerts
|

Fast-light in a photorefractive crystal for gravitational wave detection

Abstract: We demonstrate superluminal light propagation using two frequency multiplexed pump beams to produce a gain doublet in a photorefractive crystal of Ce:BaTiO(3). The two gain lines are obtained by two-wave mixing between a probe field and two individual pump fields. The angular frequencies of the pumps are symmetrically tuned from the frequency of the probe. The frequency difference between the pumps corresponds to the separation of the two gain lines; as it increases, the crystal gradually converts from normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…It is shown that the slow light could be used to implement optical switching [43], optical storage for quantum memory [31,44], optical buffer for the future all-optical communication networks [45]. And the applications of fast light are in the gravitational waves [46], absolute rotation sensing [47] and in the field of information transmission and processing [48]. Here we note that a single coherently-driven artificial atom could be not the best choice for the implementation of the tunable slow light and fast light owing to the small coefficient in front of the positive dispersion.…”
Section: Phase and Amplitude Control Of Dispersion And Absorptionmentioning
confidence: 99%
“…It is shown that the slow light could be used to implement optical switching [43], optical storage for quantum memory [31,44], optical buffer for the future all-optical communication networks [45]. And the applications of fast light are in the gravitational waves [46], absolute rotation sensing [47] and in the field of information transmission and processing [48]. Here we note that a single coherently-driven artificial atom could be not the best choice for the implementation of the tunable slow light and fast light owing to the small coefficient in front of the positive dispersion.…”
Section: Phase and Amplitude Control Of Dispersion And Absorptionmentioning
confidence: 99%
“…Moreover, fast-light has been proposed as a method to enhance the sensitivity of gravitational wave detectors. 3,4 Recently, a large slow-light effect has been demonstrated in liquid crystal light-valves, where it has been exploited the narrow bandwidth of a two-wave mixing process. 5 In the same system, adaptive holographic detection has been achieved with an extremely high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of applications, such as pulse buffering [2] and high-sensitivity interferometry [3], motivated several new directions of investigation, where the group delay of light pulses is controlled by tailoring the dispersion properties of the traversed medium. Moreover, fast light has been proposed as a method to enhance the sensitivity of gravitational wave detectors, which has been tested by employing either bifrequency Raman gain in atomic vapors [4] or doublepumped two-wave mixing in photorefractive crystals [5].…”
Section: Introductionmentioning
confidence: 99%
“…The above expression can be written as z = v g t, which means that the wave packet as a whole has to propagate with the group velocity [1] v g = d3 dk = n + 3 dnad3 Y (5) where dnad3 is the dispersion of the refractive index of the traversed medium. Formally, we can also express the group velocity as v g = n g Y (6) where n g is the group index n g = n + 3 dn d3 X…”
Section: Introductionmentioning
confidence: 99%